The China martyrs of 1900: a complete roll of the Christian heroes martyred in China in 1900 with narratives of survivors - Forsyth, Robert Coventry (The Religious Tract Society, 1904)
Contents: Boxer rising 1900 - First martyrs - Massacre at Pao Ting Fu - T'ai Yuen Fu tragedy - In deaths oft - Destitute, afflicted - Flight - Massacre at Chu-Chou-fu - Siege in Peking - Marvellous escapes - Deliverance - In hands of Boxers - Flight from Honan: Canadian Presbyterian missionaries - Flight from Honan: China Inland missionaries - Exodus from Shantung - Destruction of mission work in Manchuria - Brink of grave - Sufferings of native Christians - Mr Fei Chi Hao - Recantation - What manner of men? - Reflections - Appendices: memorial services; relief of native Christians in Shan-si; punishment of officials